Functionalized solution styrene-butadiene rubber and method for making same

By generating functionalized amino lithium initiators in situ in nonpolar solvents, the anionic copolymerization reaction of styrene and butadiene can be directly initiated, solving the problems of low storage stability and efficiency of initiators. This enables the preparation of functionalized solution-polymerized styrene-butadiene rubber with high efficiency and low cost, resulting in products with excellent performance.

CN116836335BActive Publication Date: 2026-11-06CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210305964.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-25
Publication Date
2026-11-06
Estimated Expiration
2042-03-25

AI Technical Summary

Technical Problem

In the existing technology, the functionalization modification method using lithium amino groups as initiators has problems such as poor initiator storage stability, low initiation efficiency, poor reproducibility of polymerization reaction and wide molecular weight distribution. In addition, low temperature operation increases production cost and complexity.

Method used

Functionalized amino lithium initiators are generated in situ by reacting secondary amine compounds with organolithium in a nonpolar solvent. This directly initiates anionic copolymerization in the polymerization system of styrene and butadiene, avoiding the steps of preparing and storing initiators in advance, and allowing polymerization to be carried out under mild conditions.

Benefits of technology

A highly repeatable and low-cost functionalized solution-polymerized styrene-butadiene rubber was prepared, and the product has good anti-slip properties and low rolling friction resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0003565244830000021
    Figure BDA0003565244830000021
Patent Text Reader

Abstract

The application relates to the field of solution polymerized styrene-butadiene rubber, and discloses a functionalized solution polymerized styrene-butadiene rubber and a preparation method thereof.The method comprises the following steps: carrying out contact reaction on a secondary amine compound and organic lithium in a non-polar solvent to obtain a functionalized lithium amide initiator, and then adding styrene and butadiene to in-situ initiate an anionic copolymerization reaction.The method has high repeatability, and reduces the complexity of polymerization operation and production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solution-polymerized styrene-butadiene rubber (SBR), specifically to a novel in-situ polymerization method for preparing functionalized SBR and the prepared functionalized SBR. Background Technology

[0002] In recent years, reducing fuel consumption in automobiles has received increasing attention. Functional modification of rubber compounds used in tire manufacturing can reduce hysteresis losses and lower rolling resistance.

[0003] Using functionalized initiators is one method of functionalization modification. Currently, nitrogen-containing organolithium initiators are most commonly used as functionalization initiators. However, due to the low solubility of lithium amides in nonpolar solvents, the preparation and storage of initiators are limited. Using heterogeneous lithium amides as initiators for polymerization can lead to unfavorable results such as low initiation efficiency, poor reproducibility of the polymerization reaction, and a wide molecular weight distribution of the polymer products.

[0004] Many patents employ various methods to increase the solubility of functionalized organolithium in nonpolar solvents, such as US5578542, US5643848, and EU 0709408. These methods include preparing soluble amine lithium initiators by mixing two secondary amines, adding polar additives, and introducing short-chain diene polymers into the initiator. However, these methods still cannot solve the problem of initiator storage stability.

[0005] The method described in US5714043 involves adding an organolithium compound, such as n-butyllithium, to a polymerization system containing styrene and butadiene monomers, followed by the addition of a secondary amine. This allows for in-situ polymerization initiation, yielding polymers with controllable molecular weight and molecular weight distribution. This polymerization reaction exhibits high coupling efficiency and significantly reduced product hysteresis loss. However, in this patent, the amount of secondary amine added is very small compared to the monomer. Therefore, in the initial stage of the polymerization reaction, it cannot be guaranteed that n-butyllithium will completely react with the secondary amine instead of initiating monomer polymerization. To ensure that the monomer conversion rate does not exceed 5% before the addition of the secondary amine, the aforementioned patent requires maintaining the polymerization reaction temperature at a relatively low level, preferably 0-20°C. This increases the complexity of the experimental operation and raises production costs. Summary of the Invention

[0006] This invention provides a novel in-situ polymerization method for preparing functionalized solution-polymerized styrene-butadiene rubber (SBR). This method utilizes a stable initiator that does not require prior preparation, is easy to store and handle, and initiates the anionic copolymerization reaction of styrene and butadiene in situ to obtain functionalized SBR. This method offers high reproducibility and reduces the complexity of the polymerization reaction and production costs.

[0007] To achieve the above objectives, the present invention provides a method for preparing functionalized solution-polymerized styrene-butadiene rubber, wherein the method includes: reacting a secondary amine compound with an organolithium in a nonpolar solvent to obtain a functionalized amino lithium initiator, and then adding styrene and butadiene to initiate an anionic copolymerization reaction in situ.

[0008] Preferably, the secondary amine compound has the structure shown in formula (1) or formula (2).

[0009]

[0010] In formula (1), R1 and R2 are each independently an aliphatic hydrocarbon group, alicyclic hydrocarbon group, or aromatic hydrocarbon group with 1-20 carbon atoms;

[0011] In formula (2), X is an alkylene group with 3-7 carbon atoms, and the carbon atoms in the alkylene group can be replaced by heteroatoms.

[0012] Preferably, the heteroatom is O, S, or N.

[0013] Preferably, the secondary amine compound is one or more selected from tetrahydropyrrole, azircycloheptane, diethylamine, N-ethylbenzylamine, and N-methylpiperazine.

[0014] Preferably, the molar ratio of the secondary amine compound to the organolithium (calculated as lithium) is 1:1-2, more preferably 1:1.05-1.1.

[0015] Preferably, the organolithium is one or more selected from alkyl lithium, cycloalkyl lithium, alkenyl lithium, aryl lithium, and aralkyl lithium.

[0016] Preferably, the nonpolar solvent is one or more of cyclohexane, n-hexane, n-heptane, and n-octane.

[0017] Preferably, the conditions for the contact reaction include: a contact reaction temperature of -78 to 80°C and a contact reaction time of 0.5 to 10 hours.

[0018] Preferably, the amount of the secondary amine compound is 1 × 10⁻⁶ based on the total amount of styrene and butadiene. -6 -1×10 -4 mol / g, more preferably 5×10 -6 -2×10 -5 mol / g.

[0019] Preferably, based on the total amount of styrene, butadiene, and the nonpolar solvent, the total content of styrene and butadiene is 1-30% by weight, more preferably 5-20% by weight.

[0020] Preferably, the mass ratio of styrene to butadiene is 20-40:80-60.

[0021] Preferably, the method further includes adding a structure modifier to the reaction system before the in-situ polymerization reaction begins.

[0022] Preferably, the structure modifier is one or more selected from diethyl ether, dibutyl ether, tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dioxane, crown ether, tetrahydrofurfuryl ethyl ether, tetrahydrofurfuryl butyl ether, bis(tetrahydrofurfuryl propane), triethylamine, tetramethylethylenediamine, hexamethylphosphoric triamine, potassium tert-butoxide, potassium tert-pentoxide, potassium lauryloxide, potassium alkylbenzene sulfonate, and sodium alkylbenzene sulfonate.

[0023] Preferably, the concentration of the structure modifier in the anionic polymerization system solution is 200-400 mg / kg.

[0024] Preferably, the conditions for the anionic copolymerization reaction include: a polymerization temperature of 10-160℃, a polymerization pressure of 0.05-1MPa, and a polymerization time of 1-10 hours.

[0025] According to a second aspect of the present invention, a functionalized solution-polymerized styrene-butadiene rubber prepared by the method described in the first aspect of the present invention is provided.

[0026] The above technical solution eliminates the need for prior preparation or storage of initiators. The anionic copolymerization reaction of styrene and butadiene can be initiated in situ within the same system during initiator synthesis, thus preparing functionalized solution-polymerized styrene-butadiene rubber (SBR). Furthermore, this invention eliminates the need for additional control of the initial reaction temperature, reducing operational complexity and production costs. In addition, the functionalized SBR obtained by the method of this invention exhibits good anti-slip properties and low rolling friction resistance. Detailed Implementation

[0027] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0028] According to a first aspect of the present invention, a method for preparing functionalized solution-polymerized styrene-butadiene rubber is provided, wherein the method comprises: reacting a secondary amine compound with an organolithium in a nonpolar solvent to obtain a functionalized amino lithium initiator, and then adding styrene and butadiene to initiate an anionic copolymerization reaction in situ.

[0029] According to the present invention, preferably, the secondary amine compound has the structure shown in formula (1) or formula (2).

[0030]

[0031] In formula (1), R1 and R2 are each independently an aliphatic hydrocarbon group, alicyclic hydrocarbon group, or aromatic hydrocarbon group with 1-20 carbon atoms;

[0032] In formula (2), X is an alkylene group with 3-7 carbon atoms, and the carbon atoms in the alkylene group can be replaced by heteroatoms.

[0033] Examples of aliphatic hydrocarbon groups with 1-20 carbon atoms include: methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-tridecyl, n-tetradecyl, n-pentadecanyl, n-hexadecyl, etc.

[0034] Examples of alicyclic hydrocarbon groups include cyclopropane, cyclohexane, and cycloheptane.

[0035] Examples of aromatic hydrocarbon groups include benzyl, phenethyl, and naphthylmethyl.

[0036] According to the present invention, preferably, in formula (2), X is an alkylene group having 3-5 carbon atoms, and the carbon atoms in the alkylene group may be replaced by heteroatoms.

[0037] The heteroatom is preferably O, S, or N.

[0038] In a preferred embodiment of the present invention, the secondary amine compound is one or more selected from tetrahydropyrrole, azircycloheptane, diethylamine, N-ethylbenzylamine, and N-methylpiperazine.

[0039] According to the present invention, the organolithium can be one or more of alkyl lithium, cycloalkyl lithium, alkenyl lithium, aryl lithium, and aralkyl lithium.

[0040] Preferably, the alkyl lithium is one or more of methyl lithium, ethyl lithium, isopropyl lithium, n-butyl lithium and sec-butyl lithium, more preferably n-butyl lithium and / or sec-butyl lithium.

[0041] Preferably, the cycloalkyl group is cyclopentyllithium and / or cyclohexyllithium.

[0042] Preferably, the aryl lithium and aralkyl lithium are one or more of phenyl lithium, benzyl lithium and oligostyrene-based lithium.

[0043] According to the present invention, the amount of organolithium can be selected according to the secondary amine compound. Preferably, the molar ratio of the secondary amine compound to the organolithium based on lithium is 1:1-2; more preferably, the molar ratio of the secondary amine compound to the organolithium based on lithium is 1:1.05-1.1.

[0044] In this invention, since the secondary amine compound and the organolithium can react sufficiently to obtain the functionalized aminolithium initiator, the amount of the secondary amine compound can be selected based on the amount of the monomer. Preferably, based on the total amount of styrene and butadiene, the amount of the secondary amine compound is 1 × 10⁻⁶. -6 -1×10 -4 More preferably, based on the total amount of styrene and butadiene, the amount of the secondary amine compound is 5 × 10 mol / g; -6 -2×10 - 5 mol / g.

[0045] According to the present invention, the nonpolar solvent is one or more of cyclohexane, n-hexane, n-heptane, and n-octane; preferably, the nonpolar solvent can be cyclohexane and / or n-hexane.

[0046] According to the present invention, the copolymerization reaction can also be carried out in the presence of a polar solvent, such as one or more selected from tetrahydrofuran, diethyl ether, 2-methyltetrahydrofuran, 1,4-dioxane, and ethylene glycol dimethyl ether, preferably tetrahydrofuran. Furthermore, the amount of the polar solvent used can be, for example, 1-10 equivalents of the organolithium based on lithium, preferably 2-5 equivalents.

[0047] According to the present invention, the conditions for the contact reaction include: a contact reaction temperature of -78 to 80°C and a contact reaction time of 0.5 to 10 hours; preferably, the conditions for the contact reaction include: a contact reaction temperature of 0 to 45°C and a contact reaction time of 0.5 to 2 hours.

[0048] According to the present invention, preferably, the total content of styrene and butadiene is 1-30% by weight, based on the total amount of styrene, butadiene, and the nonpolar solvent; more preferably, the total content of styrene and butadiene is 5-20% by weight, based on the total amount of styrene, butadiene, and the nonpolar solvent. Furthermore, the mass ratio of styrene to butadiene is preferably 20-40:80-60.

[0049] According to the present invention, for the purpose of adjusting the microstructure of the polymer, the method preferably further includes: adding a structure regulator to the reaction system before the in-situ polymerization reaction begins.

[0050] The structure modifier can be a conventional structure modifier used in polymerization reactions in the art, and the structure modifier can include one or more of oxygen-containing, nitrogen-containing, sulfur-containing and phosphorus-containing compounds; preferably, the structure modifier is one or more of diethyl ether, dibutyl ether, tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dioxane, crown ether, tetrahydrofurfuryl ethyl ether, tetrahydrofurfuryl butyl ether, bis(tetrahydrofurfuryl propane), triethylamine, tetramethylethylenediamine, hexamethylphosphoric triamine, potassium tert-butoxide, potassium tert-pentoxide, potassium lauryloxide, potassium alkylbenzene sulfonate and sodium alkylbenzene sulfonate.

[0051] Furthermore, the concentration of the structure modifier in the anionic polymerization system solution is 200-400 mg / kg, preferably 250-300 mg / kg.

[0052] According to the present invention, the conditions for the anionic copolymerization reaction may include: a polymerization temperature of 10-160°C, a polymerization pressure of 0.05-1 MPa, and a polymerization time of 1-10 hours; preferably, the conditions for the anionic copolymerization reaction may include: a polymerization temperature of 40-80°C, a polymerization pressure of 0.1-0.3 MPa, and a polymerization time of 1-2 hours.

[0053] According to the present invention, preferably, after the anionic copolymerization reaction, a capping agent or a coupling agent is added to obtain a double-ended or star-shaped functionalized solution-polymerized styrene-butadiene rubber.

[0054] Preferably, the capping agent is water, alcohol, dioxide, N,N,N',N'-tetraalkyldiaminobenzophenone (such as N,N,N',N'-tetramethyldiaminobenzophenone), N,N-dialkylaminobenzaldehyde (such as dimethylaminobenzaldehyde), 1,3-dialkyl-2-imidazolinone, 1-alkyl-substituted or aryl-substituted pyrrolidone.

[0055] Preferably, the coupling agent is tin tetrachloride, trialkyltin chloride, dialkyltin dichloride, alkyltin trichloride, silicon tetrachloride, etc.

[0056] According to the present invention, the method further includes adding a terminator to terminate the reaction. The terminator is selected from water or alcohols; the reaction termination time is 5-30 min, and the reaction termination temperature is 50-80°C. Preferably, the molar ratio of the terminator to the functionalized amino lithium initiator is 1.2-1.5:1.

[0057] According to the present invention, preferably, the method further includes adding an antioxidant after terminating the reaction. The antioxidant can be a conventional choice in the art. Preferably, the antioxidant is selected from phenolic antioxidants or phosphate ester antioxidants, and the amount of antioxidant used can also be a conventional amount in the art. For example, the amount of antioxidant used is 0.1-2% by weight of the reactive styrene-butadiene polymer product, preferably 0.2-1% by weight. In the present invention, after adding the antioxidant, the obtained product can be precipitated from the solution by methods such as purification precipitation, centrifugation, filtration, decantation, and hot water coagulation. Alternatively, the solvent in the reaction system can be removed by air stripping, which is known to those skilled in the art and will not be elaborated here.

[0058] According to a second aspect of the present invention, a functionalized solution-polymerized styrene-butadiene rubber prepared by the method described in the first aspect of the present invention is provided.

[0059] The present invention will be described in detail below through embodiments, but the present invention is not limited to the following embodiments.

[0060] In the following examples, the microstructure of the obtained initiator and polymer was determined using an AVANCE DRX400MHz nuclear magnetic resonance spectrometer from Bruker GmbH, Switzerland, with deuterated chloroform as the solvent.

[0061] In the following examples, the number-average molecular weight, relative molecular weight distribution, and coupling efficiency of the obtained initiator and polymer were determined using a Waters Allance 2690 gel permeation chromatography (GPC) system, with THF as the mobile phase, narrow-distribution polystyrene as the standard, and the temperature at 25°C. The coupling efficiency was defined as the ratio of the peak area corresponding to the polymer formed by coupling to the sum of the peak areas corresponding to the polymer formed by coupling and the peak areas corresponding to the remaining polymer after coupling.

[0062] Example 1

[0063] Under high-purity nitrogen protection and at room temperature (around 20°C), 5000g of a cyclohexane / n-hexane mixed solvent, 5mL of a 1.6mol / L n-butyllithium n-hexane solution, 0.67mL of tetrahydropyrrole, and 2mL of THF were added sequentially to a 10L polymerization reactor, and the mixture was stirred for 30 minutes. Then, 630g of butadiene, 204g of styrene, and 1.5mL of tetrahydrofurfuryl ether (THE) were added to the reactor. After the reaction system temperature reached 40°C, the reaction was allowed to proceed for 2 hours. A small amount of the polymerization reaction solution was taken and isopropanol was added to terminate the reaction. GPC analysis showed that M... n =123,000, M w / M n=1.32. Approximately 4 mL of 0.5 M tin tetrachloride solution was added to the reactor, and the reaction continued for 30 minutes. A small amount of the polymerization solution was then removed and isopropanol was added as a terminator. GPC analysis showed a coupling efficiency of 46%.

[0064] In addition, other polymerization reactions are terminated with isopropanol, and the polymerization solvent is removed by water precipitation coagulation to obtain wet granules, which are then dried in a two-roll mill to obtain polymer samples.

[0065] Example 2

[0066] Under high-purity nitrogen protection, 5000g of a cyclohexane / n-hexane mixed solvent was added to a 10L polymerization reactor. When the reactor temperature reached 40℃, 5mL of a 1.6mol / L n-butyllithium solution in n-hexane, 0.67mL of tetrahydropyrrole, and 2mL of THF were added, and the reaction was stirred for 30 minutes. While maintaining the reaction temperature at 40℃ and stirring, 628g of a mixed monomer of butadiene and 208g of styrene, along with 1.5mL of the structure modifier tetrahydrofurfuryl alcohol ether, were added to the reactor, and the reaction was allowed to proceed for 2 hours. A small amount of the polymerization reaction solution was taken and isopropanol was added to terminate the reaction. GPC analysis showed that M... n =131,000, M w / M n =1.38. Approximately 4 mL of 0.5 M tin tetrachloride solution was added to the reactor, and the reaction continued for 30 minutes. A small amount of the polymerization solution was then removed and isopropanol was added as a terminator. GPC analysis showed a coupling efficiency of 42%.

[0067] In addition, other polymerization reactions are terminated with isopropanol, and the polymerization solvent is removed by water precipitation coagulation to obtain wet granules, which are then dried in a two-roll mill to obtain polymer samples.

[0068] Example 3

[0069] Under high-purity nitrogen protection, 5000g of a cyclohexane / n-hexane mixed solvent was added to a 10L polymerization reactor. When the reactor temperature reached 50℃, 5mL of a 1.6mol / L n-butyllithium solution in n-hexane, 0.67mL of tetrahydropyrrole, and 2mL of THF were added, and the reaction was stirred for 30 minutes. While maintaining the reaction temperature at 50℃ and stirring, 620g of a mixed monomer of butadiene and 204g of styrene, along with 0.5mL of the structure modifier tetrahydrofurfuryl alcohol ether, were added to the reactor, and the reaction was allowed to proceed for 2 hours. A small amount of the polymerization reaction solution was taken and isopropanol was added to terminate the reaction. GPC analysis showed that M... n =133,000, M w / M n =1.36. Approximately 4 mL of 0.5 M tin tetrachloride solution was added to the reactor, and the reaction continued for 30 minutes. A small amount of the polymerization solution was then removed and isopropanol was added as a terminator. GPC measurements showed a coupling efficiency of 40%.

[0070] In addition, other polymerization reactions are terminated with isopropanol, and the polymerization solvent is removed by water precipitation coagulation to obtain wet granules, which are then dried in a two-roll mill to obtain polymer samples.

[0071] Comparative Example 1

[0072] Under high-purity nitrogen protection, 5000 g of a cyclohexane / n-hexane mixed solvent and 5 mL of a 1.6 mol / L n-butyllithium n-hexane solution were added sequentially to a 10 L polymerization reactor at room temperature, and the mixture was stirred for 30 minutes. Then, 630 g of butadiene, 204 g of styrene, and 1.5 mL of tetrahydrofurfuryl ether (THF) were added to the reactor. After the reaction system temperature reached 40 °C, the reaction was carried out for 2 hours. A small amount of the polymerization reaction solution was taken and isopropanol was added to terminate the reaction. GPC analysis showed that M... n =106,000, M w / M n =1.13. Add about 4 mL of 0.5 M tin tetrachloride solution to the reactor, continue the reaction for 30 minutes, take out a small amount of polymerization reaction solution and add isopropanol as a terminator. GPC measured the coupling efficiency to be 55%.

[0073] In addition, other polymerization reactions are terminated with isopropanol, and the polymerization solvent is removed by water precipitation coagulation to obtain wet granules, which are then dried in a two-roll mill to obtain polymer samples.

[0074] Comparative Example 2

[0075] Under nitrogen protection, 20 mL of cyclohexane / n-hexane mixed solvent, 5 mL of 1.6 mol / L n-butyllithium n-hexane solution, and 2 mL of THF were added sequentially to a dry 100 mL round-bottom flask. At room temperature, 0.67 mL of tetrahydropyrrole was slowly added dropwise using a syringe. The reaction was continued for 30 minutes while maintaining room temperature and stirring to obtain a homogeneous and clear functionalized organolithium initiator (tetrahydropyrrole alkyl lithium).

[0076] At room temperature, 5000g of cyclohexane / n-hexane mixed solvent, 630g of butadiene, and 204g of styrene were added to a 10L stainless steel polymerization reactor, along with 1.5mL of tetrahydrofurfuryl ether as a modifier. After the reaction system temperature was raised to 40℃, the aforementioned tetrahydropyrrolidinyl lithium initiator was added, and the reaction was allowed to proceed for 2 hours. A small amount of the polymerization reaction solution was taken and isopropanol was added to terminate the reaction. GPC analysis showed that M... n =146,000, M w / M n =1.47. Approximately 4 mL of 0.5 M tin tetrachloride solution was added to the reactor, and the reaction continued for 30 minutes. A small amount of the polymerization solution was then removed and isopropanol was added as a terminator. GPC measurements showed a coupling efficiency of 32%.

[0077] In addition, other polymerization reactions are terminated with isopropanol, and the polymerization solvent is removed by water precipitation coagulation to obtain wet granules, which are then dried in a two-roll mill to obtain polymer samples.

[0078] Example 4

[0079] Under high-purity nitrogen protection, at room temperature, 5000 g of a cyclohexane / n-hexane mixed solvent, 5 mL of a 1.6 mol / L n-butyllithium n-hexane solution, 0.8 mL of azircycloheptane, and 2 mL of THF were added sequentially to a 10 L polymerization reactor, and the mixture was stirred for 30 minutes. Then, 630 g of butadiene, 204 g of styrene, and 1.5 mL of tetrahydrofurfuryl ether (THE) were added to the reactor. After the reaction system temperature reached 40 °C, the reaction was carried out for 2 hours. A small amount of the polymerization reaction solution was taken and isopropanol was added to terminate the reaction. GPC analysis showed that M... n =136,000, M w / M n =1.28. Approximately 4 mL of 0.5 M tin tetrachloride solution was added to the reactor, and the reaction continued for 30 minutes. A small amount of the polymerization reaction solution was then removed and isopropanol was added as a terminator. GPC measurements showed a coupling efficiency of 45%.

[0080] In addition, other polymerization reactions are terminated with isopropanol, and the polymerization solvent is removed by water precipitation coagulation to obtain wet granules, which are then dried in a two-roll mill to obtain polymer samples.

[0081] Example 5

[0082] Under high-purity nitrogen protection, at room temperature, 5000 g of a cyclohexane / n-hexane mixed solvent, 5 mL of a 1.6 mol / L n-butyllithium n-hexane solution, 0.8 mL of diethylamine, and 2 mL of THF were added sequentially to a 10 L polymerization reactor, and the mixture was stirred for 30 minutes. Then, 630 g of butadiene, 204 g of styrene, and 1.5 mL of tetrahydrofurfuryl ether (THE) were added to the reactor. After the reaction system temperature reached 40 °C, the reaction was carried out for 2 hours. A small amount of the polymerization reaction solution was taken and isopropanol was added to terminate the reaction. GPC analysis showed that M... n =134,000, M w / M n =1.35. Approximately 4 mL of 0.5 M tin tetrachloride solution was added to the reactor, and the reaction continued for 30 minutes. A small amount of the polymerization solution was then removed and isopropanol was added as a terminator. GPC analysis showed a coupling efficiency of 39%.

[0083] In addition, other polymerization reactions are terminated with isopropanol, and the polymerization solvent is removed by water precipitation coagulation to obtain wet granules, which are then dried in a two-roll mill to obtain polymer samples.

[0084] Example 6

[0085] Under high-purity nitrogen protection, at room temperature, 5000 g of a cyclohexane / n-hexane mixed solvent, 5 mL of a 1.6 mol / L n-butyllithium n-hexane solution, 1.2 mL of N-ethylbenzylamine, and 2 mL of THF were added sequentially to a 10 L polymerization reactor, and the mixture was stirred for 30 minutes. Then, 630 g of butadiene, 205 g of styrene, and 1.5 mL of tetrahydrofurfuryl ether (THE) were added to the reactor. After the reaction system temperature reached 40 °C, the reaction was allowed to proceed for 1 hour. A small amount of the polymerization reaction solution was taken and isopropanol was added to terminate the reaction. GPC analysis showed that M... n =141,000, M w / M n =1.45. Approximately 4 mL of 0.5 M tin tetrachloride solution was added to the reactor, and the reaction continued for 30 minutes. A small amount of the polymerization reaction solution was then removed and isopropanol was added as a terminator. GPC measurements showed a coupling efficiency of 37%.

[0086] In addition, other polymerization reactions are terminated with isopropanol, and the polymerization solvent is removed by water precipitation coagulation to obtain wet granules, which are then dried in a two-roll mill to obtain polymer samples.

[0087] Example 7

[0088] Under high-purity nitrogen protection, at room temperature, 5000 g of a cyclohexane / n-hexane mixed solvent, 5 mL of a 1.6 mol / L n-butyllithium n-hexane solution, 0.9 mL of N-methylpiperazine, and 2 mL of THF were added sequentially to a 10 L polymerization reactor, and the mixture was stirred for 30 minutes. Then, 630 g of butadiene, 204 g of styrene, and 1.5 mL of tetrahydrofurfuryl ether (THE) were added to the reactor. After the reaction system temperature reached 40 °C, the reaction was carried out for 2 hours. A small amount of the polymerization reaction solution was taken and isopropanol was added to terminate the reaction. GPC analysis showed that M... n =134,000, M w / M n =1.35. Approximately 4 mL of 0.5 M tin tetrachloride solution was added to the reactor, and the reaction continued for 30 minutes. A small amount of the polymerization solution was then removed and isopropanol was added as a terminator. GPC analysis showed a coupling efficiency of 39%.

[0089] In addition, other polymerization reactions are terminated with isopropanol, and the polymerization solvent is removed by water precipitation coagulation to obtain wet granules, which are then dried in a two-roll mill to obtain polymer samples.

[0090] Example 8

[0091] Under high-purity nitrogen protection, 5000 g of a cyclohexane / n-hexane mixed solvent, 5 mL of a 1.6 mol / L n-butyllithium n-hexane solution, and 0.67 mL of tetrahydropyrrole were added sequentially to a 10 L polymerization reactor at room temperature, and the mixture was stirred for 30 minutes. Then, 630 g of butadiene, 204 g of styrene, and 1.5 mL of tetrahydrofurfuryl ether (THF) were added to the reactor. After the reaction system temperature reached 40 °C, the reaction was carried out for 2 hours. A small amount of the polymerization reaction solution was taken and isopropanol was added to terminate the reaction. GPC analysis showed that M... n =126,000, M w / M n =1.23. Approximately 4 mL of 0.5 M tin tetrachloride solution was added to the reactor, and the reaction continued for 30 minutes. A small amount of the polymerization reaction solution was then removed and isopropanol was added as a terminator. GPC measurements showed a coupling efficiency of 45%.

[0092] In addition, other polymerization reactions are terminated with isopropanol, and the polymerization solvent is removed by water precipitation coagulation to obtain wet granules, which are then dried in a two-roll mill to obtain polymer samples.

[0093] Test Example 1

[0094] The polymer samples obtained in the above examples and comparative examples were vulcanized to prepare their respective vulcanized rubbers. The vulcanization formulas are shown in Table 1. The vulcanization conditions are: roller temperature of 50°C; vulcanization temperature of 145°C; pressure of 10 MPa or more; and vulcanization time of 35 minutes.

[0095] Table 1

[0096] polymer gel 100 parts by weight Operating oil 15 portions by weight precipitate 60 parts by weight carbon black 10 portions by weight Si69 4.8 parts by weight Zinc oxide 3.0 parts by weight stearic acid 2.0 parts by weight Anti-aging agent 4010 2.0 parts by weight sulfur 1.5 parts by weight

[0097] In Table 1, the operating oil was purchased from Jinan Refinery as 200# aromatic oil; silica, carbon black, Si69, zinc oxide, stearic acid, antioxidant 4010, and sulfur are all commercially available industrial products commonly used in the rubber industry.

[0098] The tanδ value of the vulcanizate was determined using a viscoelastic spectrometer, specifically a TA-DMA2980 dynamic mechanical analyzer manufactured by Thermoanalytical Instruments, Inc., USA. Test conditions: frequency 11 Hz, heating rate 3 K / min, test temperature -80 to 80 °C. In the tire industry, the tanδ value at 0 °C is typically used to characterize wet skid resistance, while the tanδ value at 60 °C characterizes rolling friction resistance. For tread rubber, a higher tanδ value at 0 °C indicates better wet skid resistance; conversely, a lower tanδ value at 60 °C indicates lower rolling friction resistance. The test results are shown in Table 2.

[0099] Table 2

[0100]

[0101] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A process for the preparation of a functionalized solution styrene butadiene rubber, characterized in that, The method includes: reacting a secondary amine compound with organolithium in a nonpolar solvent to obtain a functionalized aminolithium initiator, and then adding styrene and butadiene to initiate an anionic copolymerization reaction in situ. The secondary amine compound has the structure shown in formula (1) or formula (2) below. Formula (1) Formula (2) In formula (1), R1 and R2 are each independently an aliphatic hydrocarbon group, alicyclic hydrocarbon group, or aromatic hydrocarbon group with 1-20 carbon atoms; In formula (2), X is an alkylene group with 3-7 carbon atoms, and the carbon atoms in the alkylene group can be replaced by heteroatoms, wherein the heteroatoms are O, S or N. The organolithium is one or more of alkyl lithium, cycloalkyl lithium, alkenyl lithium, aryl lithium, and aralkyl lithium.

2. The method according to claim 1, wherein, The secondary amine compound is one or more of tetrahydropyrrole, azircycloheptane, diethylamine, N-ethylbenzylamine, and N-methylpiperazine.

3. The method according to claim 1, wherein, The molar ratio of the secondary amine compound to the organolithium (calculated as lithium) is 1:1-2.

4. The method according to claim 3, wherein, The molar ratio of the secondary amine compound to the organolithium (calculated as lithium) is 1:1.05-1.

1.

5. The method according to any one of claims 1-4, wherein, The nonpolar solvent is one or more of cyclohexane, n-hexane, n-heptane, and n-octane.

6. The method according to any one of claims 1-4, wherein, The conditions for the contact reaction include: a contact reaction temperature of -78 to 80°C and a contact reaction time of 0.5 to 10 hours.

7. The method according to any one of claims 1-4, wherein, The amount of the secondary amine compound is 1 x 10 -6 -1 x 10 -4 mol / g, based on the total amount of styrene and butadiene.

8. The method according to claim 7, wherein, The amount of the secondary amine compound is 5 x 10 -6 -2 x 10 -5 mol / g, based on the total amount of styrene and butadiene.

9. The method according to any one of claims 1-4, wherein, Based on the total amount of styrene, butadiene, and the nonpolar solvent, the total content of styrene and butadiene is 1-30% by weight.

10. The method according to claim 9, wherein, Based on the total amount of styrene, butadiene, and the nonpolar solvent, the total content of styrene and butadiene is 5-20% by weight.

11. The method according to claim 9, wherein, The mass ratio of styrene to butadiene is 20-40:80-60.

12. The method according to any one of claims 1-4, wherein, The method further includes adding a structure modifier to the reaction system before the in-situ polymerization reaction begins.

13. The method according to claim 12, wherein, The structure modifier is one or more of the following: diethyl ether, dibutyl ether, tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dioxane, crown ether, tetrahydrofurfuryl ethyl ether, tetrahydrofurfuryl butyl ether, bis(tetrahydrofurfuryl propane), triethylamine, tetramethylethylenediamine, hexamethylphosphoric triamine, potassium tert-butoxide, potassium tert-pentoxide, potassium lauryloxide, potassium alkylbenzene sulfonate, and sodium alkylbenzene sulfonate.

14. The method according to claim 9, wherein, The concentration of the structure modifier in the anionic polymerization system solution is 200-400 mg / kg.

15. The method according to any one of claims 1-4, wherein, The conditions for the anionic copolymerization reaction include: polymerization temperature of 10-160℃, polymerization pressure of 0.05-1MPa, and polymerization time of 1-10 hours.

Citation Information

Patent Citations

  • Liquid seal bulk feeder for destructive distillation

    US5714043A

  • Process for producing modified diene-based polymer

    JP2017203120A

  • Method of producing butadiene polymers and copolymers of butadiene with styrene

    RU2644775C2

  • Functionalized initiator of anionic copolymerization and method of its obtaining, copolymers obtained using this initiator and rubber mixtures based on formed copolymers

    RU2665706C1